Hearing loss and microstructural integrity of the brain in a dementia‐free older population. Issue 11 (2nd August 2020) - Croll, Pauline H.; Vernooij, Meike W.; Reid, Robert I.; Goedegebure, André; Power, Melinda C.; Rigters, Stephanie C.; Sharrett, A. Richey; de Jong, Robert J. Baatenburg; Mosley, Thomas H.; de Groot, Marius; Lin, Frank R.; Deal, Jennifer A.
Abstract: Introduction: As hearing loss has been identified as an important risk factor for dementia, we aimed to assess the association between hearing loss and microstructural integrity of the brain. Methods: A total of 1086 dementia‐free participants (mean age = 75.2 [standard deviation: 4.9], 61.4% female) of the population‐based Atherosclerosis Risk in Communities (ARIC) study underwent hearing assessment (2016–2017) and magnetic resonance imaging of the brain (2011–2013). Microstructural integrity was determined with diffusion tensor imaging. Multivariable linear regression was used to investigate associations between hearing loss and microstructural integrity of different brain regions and white matter (WM) tracts. Results: Hearing loss was associated with lower WM microstructural integrity in the temporal lobe, lower gray matter integrity of the hippocampus, and with lower WM microstructural integrity of the limbic tracts and the uncinate fasciculus. Conclusion: Our results demonstrate that hearing loss is indepedently associated with lower microstructural integrity in brain regions that are important for different cognitive processes.